Young Adulthood Milestones and Supports Within the Context of Autism - Radey, Melissa; Anderson, Kristy A.; LaPoint, Shannon Crowley; Dolce, Emily; Killian, Michael O. (Journal of autism and developmental disorders, 2025)
The transition from childhood to adulthood is a critical developmental period in which individuals encounter profound social, institutional, and personal shifts. A diagnosis of autism can introduce unique challenges during the transition. The study described the living conditions and adult milestones of transition-age autistic young adults and compared them to their peers without autism. The analysis used Year 22 data from the Future of Families and Child Wellbeing Study (FFCWS) dataset, a national, longitudinal cohort study of children born in U.S. cities in 1998-2000. At age 22, autistic young adults were significantly more likely to report poor physical and mental health, life dissatisfaction, additional disabilities, and public assistance use compared to their non-autistic peers. Across a range of adulthood markers, including romantic relationships, independent living, full-time employment, and financial self-sufficiency, autistic young adults were less likely to achieve traditional adult milestones. The transition to adulthood remains a period of heightened vulnerability for autistic youth. Addressing these disparities will require not only improved transition planning at the individual level but also structural investments that expand access to housing, healthcare, income supports, and meaningful community inclusion.